Epidemiologia das lesões e identificação do perfil de risco para entorses sem contato de joelho e tornozelo em atletas jovens de futebol masculino - Rapello, Fabricio (2022)
Objective: to verify the influence of age (and categories) on sports injuries risk and to investigate the interactions of risk factors associated with previous and new non-contact knee and ankle sprains in male youth soccer athletes. Methods: 644 male elite youth soccer athletes, from five categories: under-20 (U-20), under-17 (U-17), under-15 (U-15), under-13 (U-13) and under-11 (U-11) years-old of a club of the Brazilian First Division were followed during the 2017 and 2018 seasons, being divided into two groups: U-11 to U-15 and U-17 to U-20. The risk of sports injuries between age groups/categories and their epidemiology (mechanism, type of event, location, type of injury, clinical diagnosis, and severity) were evaluated. Then, 81 athletes were recruited in 2019 preseason and were assessed on clinical measurements: hip internal rotation (IR) and external rotation (ER) range of motion (ROM), ankle dorsiflexion ROM, Landing Error Scoring System (LESS), modified Star Excursion Balance Test (mSEBT), Single-Leg Hop Test (SLHT) and Side Hop Test (SHT). Previous injuries were assessed by a questionnaire and new injuries were diagnosed by an orthopedic physician and were followed up for 5 months during season. Classification and regressions tree (CART) analysis was used to determine clinical predction models. Results: Overall, in 2017 and 2018 season, U-17 to U-20 athletes had a higher injury risk than U-11 to U-15 (OR = 6.16 (95% CI = 4.32, 8.77). Specifically, U-17 to U-20 had a higher risk of suffering lower-limbs injuries (OR = 4.19 (CI 95% = 3.01, 5.85), with traumatic (OR = 3.27 (CI 95% = 2.03, 5.27) and non-contact mechanism (OR = 4.03 (CI 95% = 2.56, 6.36), with moderate (OR = 2.92 (CI 95% = 2.02, 4.24) or severe (OR = 2.69 (CI 95% = 1.79, 4.05) severity and also had a higher risk of sustained hamstring strains (OR = 3.06 (CI 95% = 1.15, 8.16), anterior-cruciate ligament (OR = 7.8 (CI 95% = 1.7,35,7)) and medial-collateral ligament ruptures (OR = 5,2 (CI 95% = 1.4,18.8), and lateral ankle sprains (OR = 2.65 (CI 95% = 1.41, 4.99) than U-11 to U-15. In 2019 preseason, 25 athletes (31%) had a previous non-contact knee and ankle sprains. CART identified 3 factors associated with previous injuries: anterior reach of mSEBT, SHT and hip ER ROM. The interations of mSEBT – anterior reach > 58.85%, SHT ≤ 7.42 sec. and hip ER ROM > 56.5o (prevalence risk: 3.11 (CI 95% = 1.83-5.29) best predicted an incresead likelihood of a previous injury. This CART model had 68% of sensitivity, 87.5% of specificity and a total accuracy of 81.5%. 15 athletes (18.5 %) sustained a new non-contact knee and ankle sprains. CART identified 4 risk factors associated with new injuries: LESS, posterolateral reach of mSEBT, SHT and hip IR ROM. The interactions of a LESS score ≤ 7.5, mSEBT – posterolateral reach > 103.25% and SHT > 7.41 sec. was best risk profile at predicting a higher likelihood of sustained new injuries (relative risk: 8.62 (CI 95% = 3.76-19.81). This CART model had 80% of sensitivity, 89.4% of specificity and a total accuracy of 87.5%. Conclusions: Athletes from U-17 to U-20 categories had a higher risk of suffering an injury, in lower-limbs, with traumatic and non-contact mechanism, with moderate and severe severity, and had a higher risk of hamstring strains, ACL and MCL ruptures and lateral ankle sprains than U-11 to U-15. For previous non-contact knee and ankle sprains, interactions between mSEBT anterior reach, SHT and hip ER ROM were indicated. For new non-contact knee and ankle sprains, LESS, mSEBT posterolateral reach, SHT and hip IR ROM interacted to identify athletes in risk.